KEKUATAN ALAT BUKTI TESTIMONIUM DE AUDITU DALAM PEMBUKTIAN PERKARA GUGATAN PERCERAIAN - Novitasari, Yeni; Harjono, Harjono (Verstek, 2021)
This article examines the strength of evidence of witness testimony de auditu in the case of a divorce lawsuit in Decision Number 110/Pdt.G/2020/PN Skt and Decision Number 82/Pdt.G/2021/PN Bln. The purpose of this article is to find out the strength of evidence of De Auditu's Testimonium Witness in the divorce lawsuit case in that Decision. Based on this research, the panel of judges based on the Jurisprudence of the Supreme Court Decision number 308 K/Pdt/1959 that testimony de auditu couldn’t be used as direct evidence but could be used as evidence of presumption (vermoeden), and as a basis for proving something. In addition, the Supreme Court in decision number 239 K/Sip/1973 justified de auditu testimony except as evidence that meets the material requirements if the witness gives testimony under oath, the statement is accepted as independent evidence reaching the minimum limit of proof without other evidence if the de auditu witness consists of several people. Although it is free proof, in this case the testimony of the witness is important so that the strength of evidence is decisive evidence because de auditu witnesses played a major role in the granting of the Plaintiff's claim.  Keywords: Divorce; Evidence; Testimonium de Auditu